GDR development policy with special reference to Africa, c. 1960-1990 - Van der Heyden, Ulrich Klaus Helmut (Rhodes University, Faculty of Humanities, Department of History, 2013)
This thesis explores the political, economic and theoretical underpinnings of the German Democratic Republic's (GDR's) development policies towards the Third World between c.1960 and 1990. Particular attention is paid to Africa. Case studies of assistance to SWAPO and the ANC further focus the attention of the reader on southern Africa in particular. Aspects of both military and civilian aid are considered, including both development initiatives overseas in Africa, and development training for Africans within the GDR itself. Since German "reunification" , the GDR's history has been explored largely from a West German perspective. The present work attempts to provide a more balanced view of successes and shortcomings of the GDR's policies towards, and interaction with, African countries and liberation movements. It also aims to bring to the attention of English-speaking readers German archival sources, other primary sources and published works which they would otherwise have been unlikely to encounter. From its formation, the GDR made strenuous efforts to develop relations with countries which were either free from colonial dependency or were struggling for freedom. Over the course of thirty years, it followed a number of different approaches, and developed diverse objectives. These were shaped in the wider context of the cold war, the Hallstein doctrine (which established that the FRG "“ and, in effect, its allies - would not establish or maintain diplomatic relations with any state that recognised the GDR), the relationships between the GDR and partner socialist states, and the economic difficulties faced by the GDR. Arising from this complex situation, from time to time, both internally in the GDR and in terms of its foreign affairs, tensions and discrepancies arose between theoretical objectives and political and economic reality. Despite these severe constraints, during the period under review, the volume and range of the GDR's relationships with developing countries increased dramatically. For example, between 1970 and 1987, the number of developing countries with which the GDR had foreign economic relations on the basis of international agreements grew from 23 to 64. Viewed within its economic context, the state was arguably far more committed to development aid than the Federal Republic of Germany. In addition, there is a great deal of evidence that "solidarity" with developing nations and the oppressed enjoyed a considerable degree of popular support.
Keywords: Germany -- Foreign relations -- Africa; Germany -- Foreign economic relations -- Africa; Africa -- Foreign relations -- Germany; Africa -- Foreign economic relations -- Germany; Africa -- Politics and government -- 1960-; Africa -- History -- 1960-